2008
DOI: 10.1021/jm8003784
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the 4-Quinolone-3-carboxylic Acid Motif. 1. Synthesis and Structure−Activity Relationship of a Class of Human Immunodeficiency Virus type 1 Integrase Inhibitors

Abstract: A set of 4-quinolone-3-carboxylic acids bearing different substituents on the condensed benzene ring was designed and synthesized as potential HIV-1 integrase inhibitors structurally related to elvitegravir. Some of the new compounds proved to be able to inhibit the strand transfer step of the virus integration process in the micromolar range. Docking studies and quantum mechanics calculations were used to rationalize these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(81 citation statements)
references
References 12 publications
2
76
0
Order By: Relevance
“…Illingworth and coworkers implemented QM/MM derived induced charges into a classical framework, redocked 12 difficult protein-ligand complexes with AutoDock [116], and found that there was no significant improvement in RMSD of the lowest energy structure against the crystal structure but an increment of the largest cluster size [117]. Pasquini and coworkers explained different binding affinities of similar compounds to HIV-1 IN by calculating the partial charges of these compounds and attributed the difference to a poor interaction of the molecules with the divalent metal ions of the active site due to the electron-withdrawing effect [7]. Instead of using fixed and point-charge model, Wang and coworkers calculated solvation free energies of 31 small neutral molecules from QM charge density and continuum dielectric theory (finitedifference PB equation) [118].…”
Section: Qm-derived Partial Chargesmentioning
confidence: 99%
See 1 more Smart Citation
“…Illingworth and coworkers implemented QM/MM derived induced charges into a classical framework, redocked 12 difficult protein-ligand complexes with AutoDock [116], and found that there was no significant improvement in RMSD of the lowest energy structure against the crystal structure but an increment of the largest cluster size [117]. Pasquini and coworkers explained different binding affinities of similar compounds to HIV-1 IN by calculating the partial charges of these compounds and attributed the difference to a poor interaction of the molecules with the divalent metal ions of the active site due to the electron-withdrawing effect [7]. Instead of using fixed and point-charge model, Wang and coworkers calculated solvation free energies of 31 small neutral molecules from QM charge density and continuum dielectric theory (finitedifference PB equation) [118].…”
Section: Qm-derived Partial Chargesmentioning
confidence: 99%
“…At the same time, interest for QM in CADD has spurred further methodological development of QM methods and in particular QM approaches for docking, scoring, improvement of known lead compounds, and unraveling the reaction mechanism. As an example, QM calculations were performed to investigate significant differences in binding affinities upon modification of a CH 2 linker into a carbonyl [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among those, compound x, characterized by a completely new scaffold, showed very moderate in vitro activity inhibiting the overall integration reaction (IC 50 ¼ 164 mM). Lead optimization increased the activity to the lower micromolar range, but, unfortunately, antiviral activity at subcytotoxic concentrations in cell culture could so far not be achieved [51,52].…”
Section: Integrase Binding Inhibitorsmentioning
confidence: 99%
“…In order to understand the structure-activity relationship influencing the anti-IN activity of 4-quinolone-3-carboxylic acids, various modifications were introduced at the N-1 and C-6 positions. 83 Introduction of a dichloro substitution in the benzyl ring enhanced activity, while removal of the spacer between the two aromatic groups proved unfavorable. Increasing the hydroxyalkyl chain length at N-1 significantly improved IN inhibitory activity.…”
Section: Quinolone 3-carboxylic Acid and Derivativesmentioning
confidence: 99%